2012
DOI: 10.1158/0008-5472.can-11-3605
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ras/PI3K/ERK Pathway Induces c-Myc Stabilization to Upregulate Argininosuccinate Synthetase, Leading to Arginine Deiminase Resistance in Melanoma Cells

Abstract: Melanomas and other cancers that do not express argininosuccinate synthetase (AS), the rate-limiting enzyme for arginine biosynthesis, are sensitive to arginine depletion with pegylated arginine deiminase (ADI-PEG20). However, ADI resistance eventually develops in tumors due to AS upregulation. Although it has been shown that AS upregulation involves c-Myc, the underlying mechanisms remain unknown. Here we show that ADI-PEG20 activates Ras signaling and the effector ERK and PI3K/AKT/GSK-3β kinase cascades, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
189
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(208 citation statements)
references
References 49 publications
14
189
0
Order By: Relevance
“…We further demonstrated that upregulation of c-Myc follows the signal transduction mechanism involving Ras→PI3K/Akt/ERK→GSK3β, where ERK phosphorylates c-Myc, resulting in c-Myc accumulation by suppressing proteasomal degradation 59 . However, how Arg-auxotrophic stress is sensed in activating the Ras signal is not known.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…We further demonstrated that upregulation of c-Myc follows the signal transduction mechanism involving Ras→PI3K/Akt/ERK→GSK3β, where ERK phosphorylates c-Myc, resulting in c-Myc accumulation by suppressing proteasomal degradation 59 . However, how Arg-auxotrophic stress is sensed in activating the Ras signal is not known.…”
Section: Introductionmentioning
confidence: 69%
“…To investigate whether activation of receptor tyrosine kinases (RTK) is involved in Arg-auxotrophic response that activates Ras signaling 59 , we used lysates of A2058 cells treated with or without ADI for 15 min to probe an array of 42 anti-phosphotyrosine receptor antibodies in duplicate and observed that Axl was the predominant RTK activated (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…41 Some PIM responder cell lines identified here are known to harbor oncogenic fusion tyrosine kinases, including BCR-ABL in HNT34, FGFR1OP2-FGFR1 in KG1, and FIP1L1-PDGFRA in EOL1, which may cooperate with PIM kinases to maintain maximum STAT5 activation and prolonged MYC half-life. To evaluate whether these fusion kinases cooperate with PIM to enhance cell growth, we treated BCR-ABL-positive HNT34 cells with the combination of compound C and imatinib.…”
Section: Pim Inhibitors Impede Growth Of Cd25-positive Aml 1781mentioning
confidence: 83%
“…The hypothetical effector involved in c-Myc upregulation could act either directly or indirectly via manipulation of the many pathways Toxoplasma infection is known to impact, such as STAT-3 (1, 47), NF-B (15,48), PI3 kinase (49,50), and MAP kinases (36,39,51). Our results with the ROP16, GRA15, and GRA24 knockouts indicate that these effectors are not responsible for the Toxoplasma-dependent c-Myc induction, suggesting that STAT-3, NF-B, and p38 MAP kinase are not involved in c-Myc induction in infected cells.…”
Section: Discussionmentioning
confidence: 99%